VACTERL associated with a rare limb anomaly combined with edward (trisomy 18) syndrome - Zaheer Hasan; Vinit Kumar Thakur; Digamber Chaubey; Sandip Kumar Rahul; Sujit Kumar (Wolters Kluwer Medknow Publications, 2021)
VACTERL association is a heterogeneous condition that includes at least three out of six core structural defects which occur together more commonly than would be expected by chance alone. We report a rare association of VACTERL with unilateral proximal focal femoral deficiency and trisomy 18 syndrome.